An Overview of Bite mark Analysis - Bhargava, Kalyani; Bhargava, Deepak; Rastogi, Pooja; Paul , Mayura; Paul, Rohit; H G, Jagadeesh; Singla , Amita (Journal of Indian Academy of Forensic Medicine, 2012)
Human bite mark analysis is by far the most demanding and complicated part of Forensic  Dentistry. Although bite marks of an individual do have uniqueness due to specific characteristics and  arrangement of the teeth, when it comes to bite mark analysis, it is complicated by numerous factors,  being presented as a challenge to the Forensic Odontologists. The aim of this paper is to give a brief  overview of bite mark analysis: its usefulness and limitations. The study and analysis of such injuries is  challenging and complex. The correct protocol for collection, management, preservation, analysis and  interpretation of this evidence should be employed if useful information is to be obtained for the courts. This article throws light on the details of evidence collection techniques and step by step method  to analyse the bite mark injury. It also provides insight about the modern methods now implemented in  the analysis of bite marks. Conclusions from the analysis of bite mark evidence can assist the justice  system to answer crucial questions about interaction between people present at the scene of crime.
Keywords: Bite marks; Evidence; Comparison; Analysis